Use of Cyanex 923 for Estimation of Pd(II) - Mathias, Elton; Raman, Bhanu; Vaidya, S.P. (Asian Journal of Chemistry, 2010)
A detailed study of extraction of palladium was carried out using Cyanex 923 in chloroform as an extractant. The Pd(II) content in the extracted pink coloured complex can be estimated using direct spectrophotometric method. Various parameters for extraction of palladium were studied in detail, including the effects of HCl, SnCl2, reagent concentrations, various diluents and equilibration period. These conditions were optimized to obtain quantitative extraction. The probable nature of the extracted species was found out by a plot of log D vs. log C. The spectroscopic analysis of the complex was also done using IR, 1H NMR and 31P NMR techniques. Interference of foreign ions on extraction of Pd(II) was studied. The method can be used to separate Pd(II) from Mn(II), Ni(II), Co(II) and Fe(III) in their binary mixtures.